2007
DOI: 10.2135/cropsci2006.07.0500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Traffic Stress by the Brinkman Traffic Simulator and Cady Traffic Simulator on a Kentucky Bluegrass Stand

Abstract: The Brinkman Traffic Simulator (BTS) has been a useful tool to simulate sports field traffic. However, rate of traffic stress produced by the BTS, a pull‐behind unit with two differentially connected studded rollers, has been questioned. The Cady Traffic Simulator (CTS), a modified walk‐behind core cultivation unit, was developed and tested to potentially produce more aggressive traffic stress. A comparison study was initiated between the BTS and CTS to evaluate these simulators on a Kentucky bluegrass (Poa pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Houlbrooke et al [45] showed that ryegrass root growth was not significantly reduced as BD increased from 0.9 to 1.2 Mg/m 3 . It is noted that the compaction effort was applied only once, and compounded effects can be anticipated for continuous traffic, which would lead to increased BD and decreased turf growth and performance [12,46]. There was a significant (p < 0.001) interaction between soil type and sand layering on root zone BD (Table 6).…”
Section: Bulk Densitymentioning
confidence: 99%
“…Houlbrooke et al [45] showed that ryegrass root growth was not significantly reduced as BD increased from 0.9 to 1.2 Mg/m 3 . It is noted that the compaction effort was applied only once, and compounded effects can be anticipated for continuous traffic, which would lead to increased BD and decreased turf growth and performance [12,46]. There was a significant (p < 0.001) interaction between soil type and sand layering on root zone BD (Table 6).…”
Section: Bulk Densitymentioning
confidence: 99%
“…Topdressing applications were applied using a Mete-R-Matic self-propelled topdresser (Turfco, Minneapolis, MN) at a 0.6-cm depth (9.8 kg m j2 [dry weight]) per application, providing a cumulative sand layer depth of 2.4 cm across all treatments on August 15, 2007. At the conclusion of the cumulative sand topdressing applications, traffic was applied to all treatments from October 10 to November 3, 2007, using the Cady traffic simulator, a modified core cultivation unit (Aero King 30; Jacobsen, Charlotte, NC) (Henderson et al, 2005b;Vanini et al, 2007). Two passes forward and two passes backward (four passes) were applied per week for a total of 16 passes in 2007.…”
Section: Topdressing and Traffic Simulation (2007)mentioning
confidence: 99%
“…Turfgrass Reestablishment, Topdressing, and Traffic (2008) On April 22, 2008, treatments were core cultivated and interseeded and fertilized, similar to the procedure used by Vanini et al (2007) and Rogers et al (1998) (specifics on these practices are within Kowalewski, 2010).…”
Section: Topdressing and Traffic Simulation (2007)mentioning
confidence: 99%
“…This BTS traffic intensity corresponds to typical foot-traffic frequency at sports fields. Similar traffic treatments were used by other authors in their investigations into the wear resistance of sports turfgrasses (Kowalewski et al, 2013;Martiniello, 2007;Vanini et al, 2007).…”
Section: Traffic Simulationmentioning
confidence: 83%
“…The quantitative data are generally more accurate than the subjective data, but the time and costs associated with collecting this information limits its use. The most often used quantitative method is individual plant counts within the collected plug (Trenholm et al, 2000;Vanini et al, 2007). In recent years, digital image analysis has been more frequently and effectively used to measure turfgrass cover.…”
Section: Discussionmentioning
confidence: 99%